2019
DOI: 10.4293/jsls.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Deconstructive Teaching in the Training of Laparoscopy

Abstract: Background and Objectives: Skills-lab training is crucial for the development of advanced laparoscopic skills. In this study, we examined whether a systematic deconstructive and comprehensive tutoring approach improves training results in laparoscopic suturing and intracorporeal knot tying. Methods: Sixteen residents in obstetrics and gynecology participating in structured skills-lab laparoscopy training were randomized in 2 equal-sized groups receiving 1-on-1 tutoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
(29 reference statements)
1
15
0
1
Order By: Relevance
“…The teaching approach in the control groups was described as traditional Halsted teaching (Balafoutas et al, 2019;Romero et al, 2018), peer teaching or student tutors Notes. a if multiple procedures or assessments were used in the primary studies the included procedures and assessments within this systematics review are underlined.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The teaching approach in the control groups was described as traditional Halsted teaching (Balafoutas et al, 2019;Romero et al, 2018), peer teaching or student tutors Notes. a if multiple procedures or assessments were used in the primary studies the included procedures and assessments within this systematics review are underlined.…”
Section: Included Studiesmentioning
confidence: 99%
“…The results of these studies are not always consistent. Some trials have reported findings in favour of Peyton's approach (e.g., Balafoutas et al, 2019;Rossettini et al, 2017). Rossettini et al (2017) showed that acquisition of a cervical mobilisation technique was considerable higher in the Peyton group compared to a standard teaching group.…”
Section: Introductionmentioning
confidence: 99%
“…Four different sub-groups were identified. First, 9 studies compared Peyton's teaching approach against a standard teaching approach (Balafoutas et al 2019;Gradl-Dietsch et al 2016;Jenko et al 2012;Krautter et al 2011;Lapucci et al 2018;Lund et al 2012;Orde et al 2010;Romero et al 2018;Rossettini et al 2017). The analysis showed an effect size of 0.5 SMD (95%CI 0.13 to 0.87) in favour of the Peyton group.…”
Section: Performance -Post-acquisition Testmentioning
confidence: 99%
“…The study of Herrmann-Werner et al (2013) used a best practice skills laboratory, which consisted of structured individual feedback, performance on manikins and Peyton's teaching approach supervised by student tutors. Three studies (Gradl-Dietsch et al 2019; Gradl-Dietsch et al 2018; Münster et al 2016) used peer or student teachers for the teaching events and Ruesseler et al (2019) used a video 4-step approach.The teaching approach in the control groups was described as traditional Halsted teaching(Balafoutas et al 2019;Romero et al 2018), peer teaching or student tutors teaching(Gradl- Dietsch et al 2019;Gradl-Dietsch et al 2018;Herrmann-Werner et al 2013;Münster et al 2016), 2-stage teaching approach(Jenko et al 2012), Orde's 2-step method(Lapucci et al 2018;Orde et al 2010), standard instructions(Gradl-Dietsch et al 2016;Krautter et al 2011), traditional bedside teaching…”
mentioning
confidence: 99%
“…Some trials have reported findings in favour of Peyton's approach (e.g. Balafoutas et al 2019;Rossettini et al 2017). Rossettini et al (2017) showed that acquisition of a cervical mobilisation technique was considerable higher in the Peyton group compared to a standard teaching group.…”
Section: Introductionmentioning
confidence: 99%